(untitled) (Jahangirnagar University Journal of Biological Sciences, 2016)
Survey was conducted in four different areas viz. Jahanginagar University Campus, Gerua, Nabinagar and Chandra of Bangladesh from October 2012 to September 2013. A total of 100 species of butterflies under 9 families were identified. The maximum number of butterflies (31 species) was recorded under the family Lycaenidae followed by Nymphalidae (17 species), Pieridae (16 species), Hesperiidae (15 species), Satyridae (7 species), Papilionidae (7 species), Danaidae (5 species) and 1 species to each family of Acraediae and Amathusiidae. Species diversity was higher from summer to early monsoon and declined in late winter. Out of four areas, the highest number of butterfly was recorded at Jahangirnagar University campus followed by Gerua, Nabinagar and the lowest at Chandra. Out of 100 species, 7 were very common, 12 were common, 17 were rare, 64 were very rare. Dusky Part Wing (Psolos fuligo Mabille, 1876) under the family Hesperiidae was recorded for the first time in Bangladesh. Jahangirnagar University J. Biol. Sci. 4(1): 27-40, 2015 (June)